Biofortification in China: policy and practice - Wittenmyer Brian F; Campos-Bowers Monica H (BMC, 2007)
Abstract Micronutrient deficiency undernutrition, due to insufficient levels of vitamins and minerals in the diet, remains one of the most prevalent and preventable nutritional problems in the world today. Micronutrient undernutrition is the most common form of malnutrition. Compared to the 180 million children with protein-energy malnutrition, 3.5-5 billion persons are iron-deficient, and 140-250 million persons are vitamin A-deficient. Micronutrient deficiencies diminish physical, cognitive, and reproductive development. Undernutrition is both a cause and a result of poor human health and achievement. Middle-income nations, such as China, also suffer from micronutrient undernutrition's effects. In China's poor western provinces, despite supplementation and fortification efforts, stunting and underweight (symptoms of micronutrient undernutrition) remain common. In recent decades, nutritional adequacy, in terms of available food energy, improved immensely, as the government made food security a top priority. A potential next step for China could be to address specifically micronutrient undernutrition. The paper aims to provide a discussion of policy issues relevant to biofortification, if China were to consider the implementation of this intervention in its rural provinces. Traditional nutritional interventions currently employ four main strategies: dietary modification, supplementation, commercial fortification, and biofortification. Biofortification, a relatively new technique, involves selectively breeding staple plant varieties to increase specific nutrient levels in plant tissues. Biofortification has the potential to provide benefits to humans, plants, and livestock; nourish nutrient-depleted soils; and help increase crop yields per acre. Biofortification methods include selective breeding, reducing levels of anti-nutrients, and increasing levels of substances that promote nutrient absorption. If China were to implement biofortification programs, with help from government agencies and international organizations, several policy questions would need to be addressed. The paper discusses several policy questions that pertain to the relationship between biofortified and genetically modified crops, human health and safety concerns, labeling of biofortified crops for consumers, consumer rights, potential environmental impacts, intellectual property rights, seed disbursement, government investment, private-sector research, and additional agricultural and commercial regulations. Biofortification has the potential to help alleviate the suffering, death, disability, and failure to achieve full human potential that results from micronutrient undernutrition-related diseases.